Macrophage-Derived Exosomes Promote Bone Mesenchymal Stem Cells Towards Osteoblastic Fate Through microRNA-21a-5p - Liu, Kun; Luo, Xin; Lv, Zhao-Yong; Zhang, Yu-Jue; Meng, Zhen; Li, Jun; Meng, Chun-Xiu; Qiang, Hui-Fen; Hou, Cai-Yao; Hou, Lei; Liu, Feng-Zhen; Zhang, Bin (Frontiers in Bioengineering and Biotechnology, 2022)
The effective healing of a bone defect is dependent on the careful coordination of inflammatory and bone-forming cells. In the current work, pro-inflammatory M1 and anti-inflammatory M2 macrophages were co-cultured with primary murine bone mesenchymal stem cells (BMSCs), in vitro, to establish the cross-talk among polarized macrophages and BMSCs, and as well as their effects on osteogenesis. Meanwhile, macrophages influence the osteogenesis of BMSCs through paracrine forms such as exosomes. We focused on whether exosomes of macrophages promote osteogenic differentiation. The results indicated that M1 and M2 polarized macrophage exosomes all can promote osteogenesis of BMSCs. Especially, M1 macrophage-derived exosomes promote osteogenesis of BMSCs through microRNA-21a-5p at the early stage of inflammation. This research helps to develop an understanding of the intricate interactions among BMSCs and macrophages, which can help to improve the process of bone healing as well as additional regenerative processes by local sustained release of exosomes.